X-ray radiation shielding: enhanced performance with BaCO3 nanocrystal-infused composite polyester/PVA/BaCO3 exhibiting medicine capsule-like structure - Ardiansyah, Ardiansyah; Armynah, Bidayatul; Heryanto, Heryanto; Sukaryo, Sulistiyoso Giat; Abdul Karim, Muhammad Khalis; Tahir, Dahlang (Elsevier, 2024)
The advanced technology for effective X-ray radiation shielding is increasingly important. The use of new materials and innovative strategies has the potential to revolutionize radiation shielding, making it safer due to its outstanding characteristics. Herein, the effect of using nanocrystals of BaCO3 in a composite polyester/PVA/BaCO3 with medicine capsule-like structure are reported. Our findings showed that the BCO60 composite had an excellent shielding characteristic, it was able to attenuate half of the incoming photon energy for only 0.028 cm form their thickness. We compared our experimental findings to theoretical values through the Phy-X/PSD online software and show a very good match. The medicine capsule-like environmentally inspired X-ray radiation shield provides new strategies for design and preparation X-ray radiation shielding in the future.